2020
DOI: 10.1080/19336950.2020.1859753
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic separation is a suitable method for electrophysiology and ion channel pharmacology studies on T cells

Abstract: Ion channels play pivotal role in the physiological and pathological function of immune cells. As immune cells represent a functionally diverse population, subtype-specific functional studies, such as single-cell electrophysiology require proper subset identification and separation. Magneticactivated cell sorting (MACS) techniques provide an alternative to fluorescence-activated cell sorting (FACS), however, the potential impact of MACS-related beads on the biophysical and pharmacological properties of the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…As a result, the free binding sites can be used to determine T cells via the CD3 molecule [ 33 ]. In line with these data, T-helper cells isolated by CD4-REAlease ® were reported to be suitable for electrophysiology and ion channel studies [ 34 ] and we showed previously that CD14-TACS ® separation of monocytes yielded intact cells that can be used to generate functional dendritic cells [ 4 ].…”
Section: Discussionsupporting
confidence: 56%
“…As a result, the free binding sites can be used to determine T cells via the CD3 molecule [ 33 ]. In line with these data, T-helper cells isolated by CD4-REAlease ® were reported to be suitable for electrophysiology and ion channel studies [ 34 ] and we showed previously that CD14-TACS ® separation of monocytes yielded intact cells that can be used to generate functional dendritic cells [ 4 ].…”
Section: Discussionsupporting
confidence: 56%
“…The IMS technology has been demonstrated to have the following qualities: high sensitivity, excellent specificity and a rapid separation speed [178]. Among the disadvantages of IMS approaches is the difficulty of isolating complex phenotypes [179]. Immunomagnetic separation and fluorescence-activated cell sorting both have known or unknown drawbacks.…”
Section: Immunomagnetic Separation Technology (Ims)mentioning
confidence: 99%
“…The hKv1.2 current was recorded in CHO cells, which heterologously expressed the hKv1.2 ion channel, and hKv1.3 current was recorded in the human peripheral blood lymphocytes. The stimulation of the hKv1.3 channel expression (activation of isolated mononuclear cells by PHA, see the Materials and Methods section) and recording conditions (no Ca 2+ in the pipette to elicit Ca 2+ -activated K + channels) guaranteed that the current recorded in these cells is K + current through Kv1.3 ( Varga et al, 2012 ; Bartok et al, 2014 ; Tajti et al, 2021 ). A custom-built perfusion system was used to apply toxins at a very small perfusion rate of 200 µl/min.…”
Section: Resultsmentioning
confidence: 99%